Growth of ZnO nanorods for solar cell applications - Huynh, Phuoc Tho. (2012)
Zinc oxide nanorods have been successfully synthesized by vapor-liquid-solid (VLS) and hydrothermal growth under different conditions. It was confirm that, for low cost and simple processing, a seeding layer of ZnO is essentially needed on the substrates prior to the growth of nanorods so that types of substrates are not limited. In the VLS approach, gold catalyst and seeding film were used to grow nanorods with relatively large diameters. In the hydrothermal approach, different seeding layer preparation techniques were employed including solution droplet coating, spin coating and sputtering deposition.